Grammatical Features in Indonesia English: A Study of Indonesian College Students - Ni Luh Putu Sri Adnyani; Kadek Eva Krishna Adnyani; Veronika Genua; Sebastianus Menggo; I Nyoman Pasek Hadisaputra5 (Mimbar Ilmu, 2023)
This study aims to expose detailed descriptions of the grammatical features of Indonesian English. Indonesian English refers to a newly recognised linguistic variety of English as proposed by Coleman (2017). The grammatical characteristics as the result of acquiring a new language lead to the presence of a new variety of Indonesian English. Applying descriptive qualitative research, the data were collected based on recordings of the speech of 24 college students on three different topics. Following the principle proposed by Cogo and Dewey (2012), this study reveals twelve grammatical features as the characteristics of Indonesian English. They are namely the over-generalisation and omission of the copula BE (i.e am, is, are), the use of Indonesian collocation and literal translation, subject–verb agreement, the omission of the plural marker 's', assigning different lexical meanings, inappropriate prepositions, the omission of possessive markers, the omission and addition of articles, the application of verb tenses, the use of Indonesian acronyms and abbreviations, the incorrect construction of passive forms, and the use of Indonesian lexical items. It is shown that one of the main factors in the emergence of this new English variant is the contact of the multiple languages used by the speakers.